Kinetic studies on biliverdin-IXalpha reductase - Franklin, Edward (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2006)
The species distribution of biliverdin-IXa reductase (BVR-A) has been reinvestigated. It appears increasingly likely that birds and amphibia have the potential to express an active biliverdin-IXa reductase. The full length cDNAs encoding human, Danio rerio, murine, and Xenopus BVR-A were successfully amplified and cloned into various expression vectors. To date human BVR-A pET41a-Mod, murine BVR-A ppMAL, and Xenopus BVR-A pGEX-KG transformed cultures have been induced with IPTG resulting in the expression of recombinant proteins which display the appropriate molecular weights. The cloning and expression of an active Xenopus BVR-A in this study and the detection of biliverdin reductase activity in turkey erythrocyte cytosol extends the phylogenetic distribution of BVR-A to include amphibians and possibly birds.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin